"Frozen in Time": The Impact of Native American Media Representations on Identity and Self‐Understanding. (March 2015) - Leavitt, Peter A.; Covarrubias, Rebecca; Perez, Yvonne A.; Fryberg, Stephanie A.; Mastro, Dana; Tukachinsky, Riva
<x xml:space="preserve">Abstract</x> Mass media plays a substantial role in the way social groups understand themselves and are understood by others. Some social groups, like Native Americans, are rarely portrayed in mass media and, in the rare cases they appear, they are typically depicted in a stereotypical and historical fashion. The lack of contemporary representation of Native Americans in the media limits the ways in which Native Americans understand what is possible for themselves and how they see themselves fitting in to contemporary domains (e.g., education and employment) of social life. In this article, we contend that the invisibility of Native Americans in the media undermines self‐understanding by homogenizing Native American identity, creating narrow and limiting identity prototypes for Native Americans, and evoking deindividuation and self‐stereotyping among contemporary Native Americans.